2022
DOI: 10.3389/fphar.2022.942178
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic short-chain peptide analogues of H1 relaxin lack affinity for the RXFP1 receptor and relaxin-like bioactivity. Clues to a better understanding of relaxin agonist design

Abstract: The peptide hormone relaxin (RLX), also available as clinical-grade recombinant protein (serelaxin), holds great promise as a cardiovascular and anti-fibrotic agent but is limited by the pharmacokinetic issues common to all peptide drugs. In this study, by a computational modelling chemistry approach, we have synthesized and tested a set of low molecular weight peptides based on the putative receptor-binding domain of the B chain of human H1 RLX isoform, with the objective to obtain RLX analogues with improved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…Unlike our previous work on the H3 relaxin B chain [ 29 ], the rigid HC staple dramatically reduced the binding affinity of B7-33 analogs. Our data confirm the previous findings from the Rovero group, where they showed triazole conformationally constrained B-chain analogs of H2 relaxin exhibit significantly reduced RXFP1 activity compared with non-stapled B7-33 [ 30 ]. These results suggest that B7-33 requires a certain degree of flexibility to adopt a high-affinity binding state for RXFP1/7BP.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Unlike our previous work on the H3 relaxin B chain [ 29 ], the rigid HC staple dramatically reduced the binding affinity of B7-33 analogs. Our data confirm the previous findings from the Rovero group, where they showed triazole conformationally constrained B-chain analogs of H2 relaxin exhibit significantly reduced RXFP1 activity compared with non-stapled B7-33 [ 30 ]. These results suggest that B7-33 requires a certain degree of flexibility to adopt a high-affinity binding state for RXFP1/7BP.…”
Section: Resultssupporting
confidence: 92%
“…The finding that Aib incorporation reduced helical propensity was unexpected, suggesting that sites of incorporation are important to determine the effect on the helicity of Aib residues. Further, the data presented here and elsewhere [ 30 ], that rigid stapling strategies are not suitable for single-chain H2 relaxin analogs, suggest that more flexible stapling strategies should be explored in the future.…”
Section: Discussionmentioning
confidence: 78%
“…Additional studies are undoubtedly required to identify the amino-acidic sequence of this molecule, as such knowledge could be exploited for the development of synthetic relaxin agonists suitable for oral formulations. In this context, we have recently shown that human H1 RLX analogs can be stabilized by intra-chain tri-azolic staples in the appropriate 3-D conformation in order to further enhance their resistance to digestive enzymes [23]. Our forthcoming study will explore whether such chemical modification can also be applied to the pRLX component to obtain an effective and digestion-resistant RLX agonist.…”
Section: Discussionmentioning
confidence: 99%